Optimum Design of Oil Lubricated Thrust Bearing for Hard Disk Drive - Mohd Danial, Ibrahim; Hashimoto, Hiromu (Japan Society for Design Engineering (JSDE), 2011)
This paper presents the application of optimization method developed by Hashimoto to design oil lubricated thrust bearings for 2.5 inch form factor hard disk drives (HDD). The designing involves optimization of groove geometry and dimensions. Calculations are carried out to maximize the dynamic stiffness of the thrust bearing spindle motor. Static and dynamic characteristics of the modeled thrust bearing are calculated using the divergence formulation method. Results show that, by using the proposed optimization method, dynamic stiffness values can be well improved with the bearing geometries not being fixed to conventional grooves.